Phytophagous insects and natural enemies in kale under organic and chemical fertilizers - Cividanes, Francisco Jorge; Silva, Karen Pereira Da [UNESP]; Martins, Ivan Carlos Fernandes; Cividanes, Terezinha Monteiro Dos Santos (Instituto Biológico, 2020)
Organic agriculture is distinguished by practices that benefit the environment and support sustainable agriculture. In the present study, leafy kale, Brassica oleracea L. var. acephala DC., was submitted to chemical and organic (castor bean cake and bovine manure) fertilization treatments aiming to verify the influence of these fertilizers on the occurrence of insect pests and natural enemies. The insects were sampled by visual examination of plants and pitfall traps. Brevicoryne brassicae (L.) and Myzus persicae (Sulzer) (Hemiptera: Aphididae) were the phytophagous insects that occurred more significantly in kale, under chemical rather than organic fertilization, whereas Harmonia axyridis (Pallas), Hippodamia convergens (Guérin-Méneville) (Coleoptera: Coccinellidae), Diaeretiella rapae (M’Intosh) (Hymenoptera: Braconidae) and spiders (Arachnida: Araneae) were abundant in kale under organic fertilizer. The study showed that castor bean cake and bovine manure as leafy kale fertilizers can reduce the use of insecticides and provide quality food.

A agricultura orgânica destaca-se pelo emprego de práticas que beneficiam o meio ambiente e aumentam a sustentabilidade na agricultura. No presente estudo, a couve-de-folha, Brassica oleracea L. var. acephala DC., foi submetida a tratamentos de adubação química e orgânica à base de torta de mamona e esterco bovino para se verificar a influência dos fertilizantes na ocorrência de insetos pragas e inimigos naturais. Os insetos foram amostrados por meio de exame visual de plantas e armadilhas tipo alçapão. Brevicoryne brassicae (L.) e Myzus persicae (Sulzer) (Hemiptera: Aphididae) foram os insetos fitófagos que ocorreram significativamente em maior número em couve sob adubação química que orgânica, enquanto Harmonia axyridis (Pallas), Hippodamia convergens (Guérin-Méneville) (Coleoptera: Coccinellidae), Diaeretiella rapae (M’Intosh) (Hymenoptera: Braconidae) e aranhas (Arachnida: Araneae) foram abundantes em couve sob adubo orgânico. O estudo evidenciou que o uso de torta de mamona e esterco bovino como adubo de couve-de-folha pode reduzir o uso de inseticidas e fornecer alimentos de qualidade.
Insetos fitófagos e inimigos naturais em couve sob adubação orgânica e química
Keywords: family farming; Brassica oleracea; biological control; fertilizers; sustainability; agricultura familiar; Brassica oleracea; controle biológico; fertilizantes; sustentabilidade